The impact of COVID-19 on human pet-relationships in Malaysia and Indonesia a public sentiment analysis - Ilias, Nazhan; Saidin, Fathrurahiman; Ahmad, Nur Indah; Waheed, Moniza; Wan Mohd Noor, Murni; Ajat, Mokrish (Scientific Veterinary Institute Novi Sad, 2024)
Human stress levels escalated amid the COVID-19 epidemic as a result of restrictions on social interactions and movement. Furthermore, due to the lack of awareness about the disease’s characteristics, numerous cases of violations of animal welfare occurred. The study is focused on the macro-level analysis regarding the impact of COVID-19 on human-pet interactions in Malaysia and Indonesia. A total of 1,829 tweets related to human-pet interactions during COVID-19 were retrieved from Twitter between March 17th and September 17th, 2020. Natural Language Toolkit (NLTK) was utilized to analyze the tweets with human moderation. The analysis revealed a large number of neutral and positive sentiments in the initial stage of the study. Later, positive public sentiment (50%, n = 27/54) rose in Malaysia significantly as the Twitter users were demanding justice for the abused animals. Meanwhile, the sentiments in Indonesia were predominantly both neutral (42%, n = 52/123) and positive (34%, n = 42/123), with the sentiment shifting after an incidence of animal cruelty went viral. Following a study in the United Kingdom reporting positive COVID-19 cases in cats, an upward trend in negative public reaction was observed in Malaysia (35%, n = 7/20) and Indonesia (48.8%, n = 40/82). In conclusion, the public sentiment regarding the impact of COVID-19 on human-pet interactions affects individuals due to the associated health risks.